In Vitro Prebiotic Potential of Opuntia humifusa Leaf Extract and Its Active Constituent - Min Sung Ko; Da Bin Eom; Chung Hyeon Lee; Tae-Eun Park; Sang Jae Lee; Cheol Hyun Kim; Hui Won Moon; Seo An Lee; Kwang Woo Hwang; So-Young Park (Molecules)
Opuntia humifusa (commonly known as Cheon-nyun-cho) has traditionally been used for its antioxidant, laxative, and immune-boosting properties, but its potential prebiotic activity remains largely unexplored. In this study, we evaluated the prebiotic potential of O. humifusa leaf and fruit extracts by assessing their effects on the growth of four Lactobacillus spp. strains. Among them, Lactobacillus paracasei KCTC 12576 exhibited the most pronounced response to the extracts and was therefore selected for further investigation. Comparative analysis demonstrated that ethanol extracts were more effective than water extracts, and leaf extracts outperformed fruit extracts in enhancing bacterial viability. Notably, the ethanol extract of O. humifusa leaves showed the strongest stimulatory effect on L. paracasei KCTC 12576 growth. Based on extraction optimization studies, 60% ethanol was identified as the most effective solvent for obtaining bioactive compounds. HPLC analysis revealed the presence of isorhamnetin 3-O-β-D-(6-O-α-L-rhamnosyl)glucoside (1) as a major flavonol glycoside in the extract. A robust and validated HPLC method was established for quantification of this compound (0.33 mg/g in the 60% ethanol extract of the leaves), supporting the standardization of the extract. These findings suggest that O. humifusa leaf extract, particularly the 60% ethanol extract, may serve as a promising natural prebiotic ingredient for use in functional foods or synbiotic formulations.